1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Application of Bessel function

  1. Mar 29, 2014 #1
    1. The problem statement, all variables and given/known data
    This is not exactly a homework problem. It is just a bump in my own spare time calculations that i can't seem to get through.

    When trying to model a drum membrane (the physical details are not important) I came up with the following equation for the radial component of the standing waves:

    [itex]R''+\frac{1}{r}R'+\left(\lambda -\frac{1}{r^2}n^2\right)R=0[/itex]
    where R is a function of r

    This is almost Bessel's differential equation except that \lambda≠1.
    My calculator tells me that the result is found by multiplying r by √λ in the input of the bessel functions, and I thought that this would be easy to show by substitution. But somehow I can't get this to work.

    2. Relevant equations

    3. The attempt at a solution
    I tried working backwards. The final result is:
    [itex]R(r)=C_1 J_n\left(r\sqrt{\lambda}\right)+C_2 Y_n\left(r\sqrt{\lambda}\right)[/itex]

    The differential equation that i know this must be a solution of is(r^2 has been multiplied through from the first equation and substituded for r√λ):
    [itex](r\sqrt{\lambda})^2\frac{d^2 R(r\sqrt{\lambda})}{d(r\sqrt{\lambda})^2}+(r\sqrt{\lambda})\frac{d R(r\sqrt{\lambda})}{d(r\sqrt{\lambda})}+\left((r\sqrt{\lambda})^2-n^2\right)R(r\sqrt{\lambda})=0[/itex]

    [itex]r^2\frac{d^2 R(r\sqrt{\lambda})}{dr^2}+r\frac{d R(r\sqrt{\lambda})}{dr}+\left(r^2\lambda-n^2\right)R(r\sqrt{\lambda})=0[/itex]

    So it looks like that this is the solution except that the input of all the funktions and funktion derivatives are multiplied by a factor. How do I proceed from here. For now I would be satisfied if I could at least be able to show that the funktion proposed by my calculator is a correct solution. If there is an elegant way then it would of course also be great to know how to spot these kinds of substitutions in the future, but those problems are often related.
    Last edited: Mar 29, 2014
  2. jcsd
  3. Mar 29, 2014 #2


    User Avatar
    Homework Helper

    That can be done, but it is much simpler to work forwards. You know you want to replace
    r^2 \frac{d^2 R}{dr^2} + r\frac{dR}{dr} + (\lambda r^2 - n^2)R = 0
    x^2 \frac{d^2 R}{dx^2} + x\frac{dR}{dx} + (x^2 - n^2)R = 0.
    This suggests [itex]x = r\sqrt{\lambda}[/itex] so that
    \frac{dR}{dr} = \frac{dR}{dx} \frac{dx}{dr}
    = \sqrt{\lambda}\frac{dR}{dx}
    and so forth.
  4. Mar 29, 2014 #3
    Well I tried this but it didn't help me. From your notation it is not clear, but very quickly the same problem arises. Here you can see where i get stuck:

    First I have to rewrite your last equation because right now it is a little ambiguous. is it R(x) or R(r)?

    \frac{dR(x)}{dr} = \frac{dR(x)}{dx} \frac{dx}{dr}
    = \sqrt{\lambda}\frac{dR(x)}{dx}
    and for compleetness:
    \frac{d^2R(x)}{dr^2} = \lambda \frac{d^2R(x)}{dx^2}

    Then we have
    r^2 \frac{d^2 R(r)}{dr^2} + r \frac{dR(r)}{dr} + (\lambda r^2 - n^2)R = 0
    r^2 \lambda \frac{d^2R(x)}{dx^2} + r \sqrt{\lambda}\frac{dR(x)}{dx} + (\lambda r^2 - n^2)R = 0

    \left(\frac{x}{\sqrt{\lambda}}\right)^2 \lambda \frac{d^2R(x)}{dx^2} +\frac{x}{\sqrt{\lambda}} \sqrt{\lambda}\frac{dR(x)}{dx} + \left(\lambda \left(\frac{x}{\sqrt{\lambda}}\right)^2 - n^2\right)R = 0
    This last equation trivially simplifies to Bessel's equation. If we can justify how we arrive at it then the problem is solved.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted